Severe acute respiratory syndrome coronavirus 2 prevalence in saliva and gastric and intestinal fluid in patients undergoing gastrointestinal endoscopy in coronavirus disease 2019 endemic areas: Prospective cross‐sectional study in Japan. Issue 1 (12th March 2021) - Miyake, Shigeta; Ashikari, Keiichi; Kato, Shingo; Takatsu, Tomohiro; Kuwashima, Hirofumi; Kaneko, Hiroaki; Nagai, Koki; Watari, Ikue; Sato, Takamitsu; Yamaoka, Yutaro; Yamamoto, Tetsuya; Ryo, Akihide; et al.
Abstract : Objectives: Gastrointestinal endoscopy (GIE) is useful for the early detection and treatment of many diseases; however, GIE is considered a high‐risk procedure in the coronavirus disease 2019 (COVID‐19) pandemic era. This study aimed to explore the rate of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) positivity in saliva and gastrointestinal fluids to which endoscopy medical staff are exposed. Methods: The study was a single‐center cross‐sectional study. From June 1 to July 31, 2020, all patients who underwent GIE at Yokohama City University Hospital were registered. All patients provided 3 mL of saliva. For upper GIE, 10 mL of gastric fluid was collected through the endoscope. For lower GIE, 10 mL of intestinal fluid was collected through the endoscope. The primary outcome was the positive rate of SARS‐CoV‐2 in saliva and gastrointestinal fluids. We also analyzed serum‐specific antibodies for SARS‐CoV‐2 and patients' background information. Results: A total of 783 samples (560 upper GIE and 223 lower GIE samples) were analyzed. Polymerase chain reaction (PCR) on saliva samples did not show any positive results in either upper or lower GIE samples. However, 2.0% (16/783) of gastrointestinal fluid samples tested positive for SARS‐CoV‐2. No significant differences in age, sex, purpose of endoscopy, medication, or rate of antibody test positivity were found between PCR positive and PCR negative cases. Conclusions: Asymptomatic patients, even those with no detectable virus in their saliva, had SARS‐CoV‐2 in their gastrointestinal tract. Endoscopy medical staff should be aware of infection when performing procedures. The study was registered as UMIN000040587.